Who killed Rasputin? - Wadding, Michael ([Australia] : BBC, 2005)
revealing a compelling new theory about the circumstances of Rasputin's death. The most famous murder case of the 20th century is reopened, as Timewatch travels to St Petersburg, Moscow, New York and Canada, to reassess history and reveal stunning new suspects implicated in the downfall of one of Russia's most notorious figures. This film poses a compelling new theory about then circumstances of Rasputin's death.
Executive producer, Bill Locke ; series editor: John Farren ; director of photography: Paul Lang.
Narrator: Michael Praed ; Rasputin played by Richard Collin
dvd format
Keywords: Rasputin, Grigori Efimovich, -- ca. 1870-1916.; Russia -- History -- Nicholas II, 1894-1917.